Hear Us - Women Affected by Political Violence in Zimbabwe Speak Out (United States : RAU ; Witness, 2009)
In 2008, political violence erupted throughout Zimbabwe as a result of the contested national elections. Zimbabwean women of all ages, targeted for their political affiliations, were abducted from their workplaces and homes, raped, tortured, and beaten in secret torture centers. It is estimated that from May to July, state-sanctioned groups raped over 2,000 women and girls. Women in Zimbabwe have historically been subjected to violence in response to involvement in elections or other political activities. Local authorities and national leaders have been unresponsive to local and international demands for an end to this violence. “Hear Us” features four of these women, who have come forward to demand justice from the Zimbabwean government and the Southern African Development Community.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films